PENGARUH PENGGUNAAN MEDIA KERETA ANGKA TERHADAP KEMAMPUAN BERHITUNG PERMULAAN PADA ANAK USIA 5-6 TAHUN DI TKK PILARIN - Theresia Kewa; G. Betty, Credo; Olga Litna, Kamelia; Yuniati, Yohana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
. This study aims to determine the effect of using number train media on the early numeracy skills of children aged 5–6 years at the Pilarin Kindergarten (TKK). The sample in this study was 23 children in Group B. This study used an experimental design with a One Group Pretest-Posttest Design. Data analysis techniques in this study consisted of prerequisite tests and hypothesis tests. The prerequisite tests conducted were normality tests and homogeneity tests. The hypothesis test used was a Paired Sample t-test. The data from this study were analyzed using SPSS Version 27. The results of this study indicate that the use of number train media in the learning process can improve early numeracy skills in early childhood. This is supported by the results of the Paired Sample t-test hypothesis test, which obtained an Asymp.Sig. (2-tailed) value of <0.001, less than 0.05. Therefore, H0 is rejected and Ha is accepted. This indicates that the use of number train media on the early numeracy skills of children aged 5–6 years at the Pilarin Kindergarten.Keywords: Media, number train, early numeracy, early childhood, TKK Pilarin Kupang